Về mối quan hệ giữa pháp luật thương mại, kinh tế và dân sự - Nghĩa, Phạm Duy (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 1, 1999)
The Vietnamese Commercial Law has taken effect since January 1, 1998 and becomes an important part of the system of the economic law in Vietnam. The author analyzes the historical background, which leads to the concept of the commercial law as a relatively independent legal subject related to the civil law. Despite considerable efforts to clarify the relation between the civil code, the commercial law and the ordinance on the economic contracts, the new law put in question the theoretical concept of the economic law as an independent legal subject. Based on the recent development of many new legal fields, such as the consumer protection, the competition law, the stock exchanges law, the author provides a new concept of the economic law and forecasts coming challenges in this legal subject.